EMPOWERING SECONDARY SCHOOL STUDENTS FOR SUSTAINABLE DEVELOPMENT IN NIGERIA (Scientific Journal of Educational Management, Research and law, 2026)
This study adopts a conceptual research design to investigate the empowerment of secondary school students for sustainable development in Nigeria. Relying on an extensive review of existing literature, national curriculum frameworks, and global educational benchmarks particularly Sustainable Development Goal 4, Target 4.7 the study critically analyses the alignment between current educational practices and the competencies required for sustainability. Data for the analysis were derived from purposively selected scholarly articles, education policy documents, and reports by UNESCO and Nigerian educational bodies. The population of the study comprises all public the secondary schools in the study area while the sampling techniques focused on stratified random sampling of 30% with 180 participants used for the study. Through qualitative content analysis, the study identifies structural gaps such as outdated curricula, inadequate teacher training, insufficient inclusion of environmental and civic education, and lack of infrastructure as key impediments to effective student empowerment. The findings revealed a significant positive relationship between study skills and critical thinking as factor for sustainable development in Nigerian secondary schools and call for urgent curriculum reform, investment in teacher capacity development, and the integration of sustainability competencies into both formal and informal educational settings. The study concludes that without a deliberate transformation of Nigeria’s secondary education landscape, the goals of sustainable national development will remain elusive.